Nanorobots: Future in dentistry - Neetha J. Shetty; P. Swati; K. David (Elsevier, 2013)
The purpose of this paper is to review the phenomenon of nanotechnology as it might apply to dentistry as a new field called nanodentistry. Treatment possibilities might include the application of nanotechnology to local anesthesia, dentition renaturalization, the permanent cure for hypersensitivity, complete orthodontic realignment in a single visit, covalently bonded diamondized enamel, and continuous oral health maintenance using mechanical dentifrobots. Dental nanorobots could be constructed to destroy caries-causing bacteria or to repair tooth blemishes where decay has set in, by using a computer to direct these tiny workers in their tasks. Dental nanorobots might be programed to use specific motility mechanisms to crawl or swim through human tissue with navigational precision, to acquire energy, to sense and manipulate their surroundings, to achieve safe cytopenetration, and to use any of a multitude of techniques to monitor, interrupt, or alter nerve-impulse traffic in individual nerve cells in real time. Keywords: Nanotechnology, Dentistry, Nanorobots, Nanorobotics